2014
DOI: 10.1007/s11356-014-3785-8
|View full text |Cite
|
Sign up to set email alerts
|

Fish embryo tests with Danio rerio as a tool to evaluate surface water and sediment quality in rivers influenced by wastewater treatment plants using different treatment technologies

Abstract: In order to evaluate surface water and the sediment quality of rivers connected to wastewater treatment plants (WWTPs) with different treatment technologies, fish embryo tests (FET) with Danio rerio were conducted using native water and sediment samples collected upstream and downstream of four WWTPs in Southern Germany. Two of these WWTPs are connected to the Schussen River, a tributary of Lake Constance, and use a sand filter with final water purification by flocculation. The two others are located on the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Oxygen saturation was always above 90% in the tested surface water samples as well as in the SSB effluent samples. The procedure for the sample preparation and test performance was the same as described in the work of Thellmann et al [ 20 ]. The tests were considered to be valid, when (1) the fertilization rate of all eggs collected was ≥70%, (2) the survival rate of embryos from the negative control was ≥90% after 96 h of exposure (3), and the hatching rate in the negative control was ≥80% after 96 h of exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Oxygen saturation was always above 90% in the tested surface water samples as well as in the SSB effluent samples. The procedure for the sample preparation and test performance was the same as described in the work of Thellmann et al [ 20 ]. The tests were considered to be valid, when (1) the fertilization rate of all eggs collected was ≥70%, (2) the survival rate of embryos from the negative control was ≥90% after 96 h of exposure (3), and the hatching rate in the negative control was ≥80% after 96 h of exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Long-term benefits of advanced wastewater treatment based on powdered activated carbon for aquatic ecosystems have already been described by Thellmann et al [47] and Triebskorn et al [72]. These studies focussed on another central European river (Schmiecha), which had been reported to be highly polluted by wastewater originating from textile industry in the second half of the twentieth century.…”
Section: Discussionmentioning
confidence: 99%
“…The respective methods used for the statistical analyses of method-specific data have been described elsewhere [25,27,30,32,35,37,43,47,54]. For the overall statistical analyses on which Figs.…”
Section: Statisticsmentioning
confidence: 99%
“…Naturally, this leads to the development of methods that are not perfectly optimized for all the determined compounds, as can be observed for example in recoveries of polar benzotriazoles ranging from 22 to 112% in [ 54 ]. In some of the reviewed papers, there is also very little to no emphasis on method optimization, since they focus more on the application and interpretation of concentrations and their changes in various environmental samples [ 5 , 6 , 52 , 55 , 56 , 57 , 58 ].…”
Section: Solid-phase Extraction Of Benzotriazoles From Aqueous Sammentioning
confidence: 99%